At town water level in the polder: District F in the Amsterdam city extension on the origin and development of a neighbourhood in the Amsterdam urban district de Pijp (Bulletin KNOB, 2012)
In 1905 the Amsterdam municipal council outlined a city extension plan for the Binnendijksche Buitenveldertsche Polder south of district YY (better known as De Pijp) on the land that had been added to Amsterdam through the annexation of large parts of the neighbouring municipality Nieuwer-Amstel in 1896. This city extension plan, designed by Hendrik Petrus Berlage in 1900, replaced the never adopted engineer’s plan of ir. C.L.M. Lambrechtsen van Ritthem. Within a sober aesthetic framework Lambrechtsen provided solutions to a wide range of technical problems related to the practice of the nineteenth-century city extensions. The main issues were in the field of water management, sewerage and infrastructure. However, around the existing city lay a wreath of built-up areas with a few older centres in them, which made more regular city extension of Amsterdam problematic, if not impossible. One of the most important of these centres was a hamlet along Amsteldijk, south of Ceintuurbaan, originally called District F. This ‘polder district’ has gone through a radical change in appearance and structure since 1896. The way in which this was realized is typical of the pragmatic approach to the phenomenon city extension at the end of the nineteenth century.The buidings in District F were built on wet, low-lying polder land. For a good connection to the existing part of Amsterdam the entire region had to be withdrawn from polder water level (‘depoldered’), i.e. discontinuing the existing polder sewers, raising (building) sites and demolishing the existing buildings at polder water level. Because of the existing buildings this was difficult, time-consuming and expensive. Compulsory purchase was taking place on a relatively limited scale. The municipality left improvement of the district to private persons, whereby raising of building sites was made compulsory for new construction. Initially, this raising per parcel led to a very irregular streetscape, less accessibility, and flooding in the lower-lying adjoining parcels. The extension of Van Woustraat was also important for the improvement of the polder district; for this purpose a lot of premises built at polder water level were demolished on the projected track. The increase in value of the surrounding parcels indirectly led to further demolition and new construction along the track, just as to declarations of unfitness for habitation of ‘unhealthy’ premises by the municipality.In the city extensions in this period the problems of water discharge and sewerage took a lot of thought. The solutions opted for left a visible mark on the character of the extension plans. The compulsory raising of sites led to problems with water discharge, for which newly dug canals could offer a solution. The canals in the extension plans of Lambrechtsen van Ritthem and Berlage formed important links in the regulation of groundwater level and sewerage. Transportation by water and aesthetic motives also played a part in the decision on digging new canals. The relocation of the canals in Berlage’s second extension plan (1915-1917) in a southward direction cannot be detached from the new sewerage pumping stations put into operation in 1913, which made it possible to move waste water, groundwater and rainwater over great distances without any problems.